Development and evaluation of a rapid and simple diagnostic assay for COVID-19 based on loop-mediated isothermal amplification. - Rokusuke Yoshikawa; Haruka Abe; Yui Igasaki; Saeki Negishi; Hiroaki Goto; Jiro Yasuda (Public Library of Science (PLoS), 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly pathogenic novel coronavirus that has caused a worldwide outbreak. Here we describe a reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay that uses a portable device for efficient detection of SARS-CoV-2. This RT-LAMP assay specifically detected SARS-CoV-2 without cross-reacting with the most closely related human coronavirus, SARS-CoV. Clinical evaluation of nasal swab samples from suspected SARS-CoV-2 pneumonia (COVID-19) patients showed that the assay could detect over 23.7 copies within 15 min with a 100% probability. Since the RT-LAMP assay can be performed with a portable battery-supported device, it is a rapid, simple, and sensitive diagnostic assay for COVID-19 that can be available at point-of-care. We also developed the RT-LAMP assay without the RNA extraction step-Direct RT-LAMP, which could detect more than 1.43 x 103 copies within 15 min with a 100% probability in clinical evaluation test. Although the Direct RT-LAMP assay was less sensitive than the standard RT-LAMP, the Direct RT-LAMP assay can be available as the rapid first screening of COVID-19 in poorly equipped areas, such as rural areas in developing countries.